Il sole del cosmo e le torte che sono chiaramente segni di pioggia: osservazioni sui nuovi Studies on the Derveni Papyrus - Walter Lapini (Noctua)
This essay deals with the recent book Studies on the Derveni Papyrus, Volume 2, edited by Glenn W. Most (Oxford, Oxford University Press, 2022). After assessing its merits and shortcomings, it makes some general points about current publishing, research ethics, and the dangers of co-optation in collaborative work.